USE OF MODERN INFORMATION TECHNOLOGIES TO IMPROVE THE QUALITY OF LESSONS - Taylakova G.B. (Journals Park Publishing, 2023)
In the field of education, the use of pedagogical and information and communication technologies, Internet information and educational resources, the conference method effectively helps students acquire knowledge at a high level and creates an opportunity for them to become qualified specialists in the future.
Keywords: Modern information technologies, independent education, technologies.